1997
DOI: 10.1104/pp.115.3.1109
|View full text |Cite
|
Sign up to set email alerts
|

RNase Activities Are Reduced Concomitantly with Conservation of Total Cellular RNA and Ribosomes in O2-Deprived Seedling Roots of Maize

Abstract: RNase activities are modulated during plant development and in response to certain abiotic and biotic cues and are expected to play a role in the regulation of RNA levels and turnover (for reviews, see Wilson, 1975;Farkas, 1982;Green, 1994). The electrophoretic and biochemical nature of a number of individual plant RNases and nucleases have been described, and knowledge of the function of specific RNases is slowly accumulating. The best-characterized plant RNases are the extracellular S-RNases and S-like RNase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Modulation of RNase activities has been expected to play a role in the regulation of RNA turnover in response to certain abiotic and biotic cues (Green, 1993;Wilson, 1975). Especially, Fennoy et al (1997) has demonstrated that a specific set of mRNAs could be conserved during O 2 deficiency through modulation of specific RNase activities in response to O 2 deprivation. If specific group of mRNAs is preferentially stabilized under anoxia by such a decrease in specific RNase activity, the resultant pattern of response would resemble that observed for the type-3 genes in Fig.…”
Section: Figmentioning
confidence: 99%
“…Modulation of RNase activities has been expected to play a role in the regulation of RNA turnover in response to certain abiotic and biotic cues (Green, 1993;Wilson, 1975). Especially, Fennoy et al (1997) has demonstrated that a specific set of mRNAs could be conserved during O 2 deficiency through modulation of specific RNase activities in response to O 2 deprivation. If specific group of mRNAs is preferentially stabilized under anoxia by such a decrease in specific RNase activity, the resultant pattern of response would resemble that observed for the type-3 genes in Fig.…”
Section: Figmentioning
confidence: 99%
“…Polysomes were isolated from cytoplasmic extracts by sucrose sedimentation. We used methods derived from the protocols developed for nuclei isolation by Blobel and Potter (1966), for cytoplasmic RNA prepara-tion by del Prete et al (2007), and for polysome isolation by Fennoy et al (1997) with minor modifications.…”
Section: Preparation Of Nuclear Cytoplasmic and Polysomal Rnasmentioning
confidence: 99%
“…An effect on the activity of RNases has also been observed in plants, following abiotic stresses such as ozone and salinity (Gomes-Filho and Sodek, 1988;Booker, 2004). An observed decrease in RNase activity in wheat (Triticum aestivum) following heat shock was hypothesized to have a role in the observed increase in mRNA stability (Chang and Gallie, 1997), whereas reduction in activity of specific RNases in response to low-O 2 stress in maize (Zea mays) roots was suggested to facilitate conservation of nontranslating ribosomes and poorly translated mRNA (Fennoy et al, 1997).…”
mentioning
confidence: 99%